Induction of osteoclast-like cell formation by leptin-induced soluble intercellular adhesion molecule secreted from cancer cells. (May 2019) - Tsai, Cheng-Fang; Chen, Jia-Hong; Wu, Chen-Teng; Chang, Pei-Chun; Wang, Shu-Lin; Yeh, Wei-Lan
Background: Leptin is considered a tumorigenic adipokine, suggested to promote tumorigenesis and progression in many cancers. On the other hand, intercellular adhesion molecule-1 (ICAM-1) shows altered expression in a variety of benign and malignant diseases. Histologically, ICAM-1 expression is reported as proportional to cancer stage and considered as a potential diagnosis biomarker. The altered expressions of ICAM-1 and its soluble form in malignant diseases have gained interests in recent years. Material and methods: The expression of ICAM-1 and its regulatory signaling were examined by Western blot or flow cytometry. The effect of soluble ICAM-1 on osteoclast formation was investigated by tartrate-resistance acid phosphatase staining of RAW cells and tumor-induced osteolysis in vivo . Results: In our study, we found that leptin enhanced soluble ICAM-1 production but not surface ICAM-1 expression in lung and breast cancer cells, and this effect was regulated through leptin receptor (ObR), while silencing ObR abrogated leptin-induced soluble ICAM-1 expression. In addition, we revealed that leptin administration provoked the JAK1/2, STAT3, FAK, ERK, and GSK3αβ signaling cascade, leading to the elevation of ICAM-1 expression. Moreover, soluble ICAM-1 secreted by leptin-stimulated cancer cells synergize with the receptor activator of nuclear factor kappa-B ligand (RANKL) in inducing osteoclast formation. Soluble ICAM also enhanced tumor-induced osteolysis in vivo . Conclusion: These findings suggest that soluble ICAM-1 produced under leptin treatment enhances osteoclast formation and is involved in tumor-induced osteolysis. Leptin plays an important role in physiology in health and diseases. Leptin affects immune responses that may induce inflammation and carcinogenesis. Leptin is also considered as a tumorigenic adipokine suggested to promote tumorigenesis and progression in many cancers. On the other hand, intercellular adhesion molecule-1 (ICAM-1) shows altered expression in a variety of benign and malignant diseases. Histologically, ICAM-1 expression is reported to be proportional to cancer stage and considered as a potential diagnosis biomarker. It has been reported that soluble ICAM-1 allows tumor cells to escape from immune recognition and stimulates angiogenesis and tumor growth. The altered expressions of ICAM-1 and its soluble form in malignant diseases have gained interests in recent years. In our study, we found that leptin enhanced soluble ICAM-1 production but not surface ICAM-1 expression in lung and breast cancer cells, and this effect was regulated through leptin receptor (ObR), while silencing ObR abrogated leptin-induced soluble ICAM-1 expression. In addition, we revealed that leptin administration provoked the JAK1/2, STAT3, FAK, ERK, and GSK3αβ signaling cascade, leading to the elevation of ICAM-1 expression. Moreover, soluble ICAM-1 secreted by leptin-stimulated cancer cells synergize with receptor activator of nuclear factor-kappa B ligand in inducing osteoclast formation. Soluble ICAM also enhanced tumor-induced osteolysis in vivo . These findings suggest that soluble ICAM-1 produced under leptin treatment is possibly involved in lung and breast cancer bone metastasis.